proteomic analysis of rice seed germination as affected by high temperature and ABA treatment - Liu, Shu‐Jun; Xu, Heng‐Heng; Wang, Wei‐Qing; Li, Ni; Wang, Wei‐Ping; Møller, Ian Max; Song, Song‐Quan (Physiologia plantarum, 2015)
Seed germination is a critical phase in the plant life cycle, but the specific events associated with seed germination are still not fully understood. In this study, we used two‐dimensional gel electrophoresis followed by mass spectrometry to investigate the changes in the proteome during imbibition of Oryza sativa seeds at optimal temperature with or without abscisic acid (ABA) and high temperature (germination thermoinhibition) to further identify and quantify key proteins required for seed germination. A total of 121 protein spots showed a significant change in abundance (1.5‐fold increase/decrease) during germination under all conditions. Among these proteins, we found seven proteins specifically associated with seed germination including glycosyl hydrolases family 38 protein, granule‐bound starch synthase 1, Os03g0842900 (putative steroleosin‐B), N‐carbamoylputrescine amidase, spermidine synthase 1, tubulin α‐1 chain and glutelin type‐A; and a total of 20 imbibition response proteins involved in energy metabolism, cell growth, cell defense and storage proteins. High temperature inhibited seed germination by decreasing the abundance of proteins involved in methionine metabolism, amino acid biosynthesis, energy metabolism, reserve degradation, protein folding and stress responses. ABA treatment inhibited germination and decreased the abundance of proteins associated with methionine metabolism, energy production and cell division. Our results show that changes in many biological processes including energy metabolism, protein synthesis and cell defense and rescue occurred as a result of all treatments, while enzymes involved in methionine metabolism and weakening of cell wall specifically accumulated when the seeds germinated at the optimal temperature.